Gersonides : Judaism within the limits of reason - Feldman, Seymour (Cambridge EBA Collection, 2010)
Gersonides (1288-1344), known also as Ralbag, was a philosopher of the first rank as well as an astronomer and biblical exegete, yet this is the first English-language study of the significance of his work for Jewish thought. Seymour Feldman, the acclaimed translator of Gersonides' most important work, The Wars of the Lord - a complete philosophical system and astronomical encyclopedia - has written a comprehensive picture of Gersonides' philosophy that is both descriptive and evaluative. Unusually for a Jewish scholar, Gersonides had contacts with several Christian notables and scholars. It is known that these related to mathematical and astronomical matters; the extent to which these contacts also influenced his philosophical thought is a matter of some controversy. Unquestionably, however, he wrote a veritable library of philosophical, scientific, and exegetical works that testify not only to the range of his intellectual concerns but also to his attempt to forge a philosophical-scientific synthesis between these secular sciences and Judaism. Unlike many modern scientists or philosophers, who either scorn religion or compartmentalize it, he did not see any fundamental discrepancy between the pursuit of truth via reason and its attainment through divine revelation: there is only one truth, with which both reason and revelation must agree. As a philosopher-scientist and biblical exegete Gersonides sought to make this agreement robustly evident. While philosophical and scientific ideas have progressed since Gersonides' time, his work is still relevant today because his attempt to make prophecy and miracles understandable in terms of some commonly held philosophical or scientific theory is paradigmatic of a religion that is not afraid of reason. His general principle that reason should function as a 'control' of what we believe has interesting and important implications for the modern reader. Indeed, some of his basic arguments are favoured by many contemporary thinkers who attempt to incorporate modern science into their religious belief system. He was not afraid to make religious beliefs philosophically and scientifically credible; one could say that he pursued an 'ethics of belief' in that he held that there are constraints to what is believable, especially in religion. In this respect he was a precursor of Kant and Hermann Cohen: Judaism is or should be a religion of reason.